Effect of Lifestyle on Consumer Decisions in Choosing Retail Business in the City of Manado - Ventje A. Senduk; Nikolas F. Wuryaningrat (Journal of International Conference Proceedings (JICP), 2019)
Shopping in the consumer retail business is often driven by the lifestyle they live. According to Lastovicka and Joachimsthaler (1988) a person's lifestyle is related to how a person lives, how they spend their money, and how they use their time in daily life which is expressed through activities, interests, and opinions (opinions) in question. As mentioned earlier consumer behavior is also influenced by lifestyle. Therefore, a good knowledge of the consumer lifestyle is important to be known by business people because it is able to provide information about what products should be offered, product innovation, promotions, and so on. The research was conducted in areas that have many retail businesses, especially modern retailers such as Malalayang, Paal 2, Boulevard, and the area around the Airport. Samples were drawn by purposive sampling method. The data collected was 96 respondents. Data were analyzed by multiple regression with SPSS version 20 software. The results showed that lifestyle simultaneously had a positive and significant effect on consumer decisions in choosing a retail business in the city of Manado. Similar results are also shown in each dimension of lifestyle, namely activity, interest and opinion have a significant influence on consumer decisions in choosing a retail business.